Sport Massage Training and Development - Alimuddin Alimuddin; Eka Mulyaningsih (Jurnal Berkarya Pengabdian Masyarakat, 2019)
Community Partnership Program "Sports Massage Training and development in Kelurahan Senga subdistrict of Luwu District" is a program to develop middle and lower community business. The purpose of this program is to (1) increase the quality and participation of the community, especially the partner in the development of sports massage business in the village Senga subdistrict Belopa District Luwu, (2) Unemployment reduction and Business opportunities in the field of sport so as to give a real contribution to the development of sports in this region mainly in the field of sports health. The Problem solving offered in this research is with the help of training and enhancement of maassage sports both in terms of improving the quality of knowledge and skills, funding assistance for equipment and in terms of management and planning Business and socialization assistance to introduce sports massage in the community, especially in the area Senga Kecamatan Belopa District Luwu District. Partners in this case still have some problems from various aspects such as management and business planning in the field of sports, quality aspects and knowledge about the sport massage is still minimal, the marketing aspect is still far from the word And capital that is still minimal to prepare the necessary tools for the implementation of the activities. Implementation of the program planned in several stages. The stages are; (1) Program Introduction to the partner, (2) preparation of infrastructure and tools, (3) training in Sport massage, (4) Conducting management training and business plan, (5) Socialization of sports massage in related agencies and networking development, (6) Program assistance, as well as (7) Monitoring and evaluation. This activity is planned to be published in journals that have ISSN, print media and mass media, as well as additional external that has been established in the research proposal of service to the community Ministry of Research, Technology, and education High.